Transforming 21st Century Education: Analysing the Implementation of Technology in Teaching and Learning - Muhammad Arsyad; Ismaul Fitroh; Muh Syamsul Arifin (Jurnal Ilmiah Edukatif, 2024)
As we journey through the 21st century, the world of education is undergoing a profound transformation fuelled by sophisticated and exotic technological advances. These rapid developments in technology open up invaluable opportunities. It promises to improve the quality and effectiveness of learning experiences, engage students at a deeper level, expand access to a wealth of learning resources, and develop skills that are crucial in this new era. In addition, technology embellishes the assessment and evaluation process, making it more effective and efficient. Moreover, it becomes a beacon of inclusivity and accessibility, ensuring that learning is accessible to all. However, the successful integration of these innovations depends on strong infrastructure, improved educator competencies, supportive policies, and collaborative efforts between all stakeholders. With a holistic and synergistic approach, the transformation of education through technology not only promises innovation and interaction; it shapes a richer and higher-quality learning environment. Such an environment nurtures the younger generation.